(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Herbal preparations are getting popular day by day as they are considered to be safe. Septiloc is also a herbal preparation which is useful in a wide range of wounds such as diabetic wounds, bed sores, ulcers, burns, post-surgical wounds etc. It was subjected to analysis by AAS-VGA for toxic heavy metals like arsenic and mercury. Levels of arsenic and mercury were estimated in ten different batches of Septiloc and evaluated with respect to permissible limit (PL) and provisional maximum tolerable daily intake (PMTDI). In most of the samples, As and Hg were either below the detection limit or below the PL and PMTDI. These results prove that Septiloc is a safe polyherbal preparation and is free from toxic effects of As and Hg.